PREVALENSI, KARAKTERISTIK DAN FAKTOR-FAKTOR YANG TERKAIT DENGAN INFEKSI SALURAN KEMIH PADA PENDERITA DIABETES MELITUS YANG RAWAT INAP - Ariwijaya, Made; Suwitra, Ketut (journal of internal medicine, 2012)
Diabetes Melitus (DM) is related with the increased risk of Urogenital Tract Infection (UTI). Prevalence and characteristic organisms from urine suprapubic aspiration in DM patient who admitted to the hospital is rare. The aim of the study was to now prevalence, characteristic and related factor with UTI in DM patient who admitted. We have done cross sectional analytic study in admitted DM patient more than 12 years old, less than 3 days admission. The patients who used antibiotic last 7 day before urine culture dan pregnancy were excluded. Urine specimen were taken via suprapubic aspiration. We had 100 responden with 53 men (53%), 47 women (47%), age 56 ± 11.9 yo., mean Body massa indeks (BMI) 23.99±2.56 Bw/ m2.SBP 130.7 ± 28.5 mmHg. DBP 80 ± 14.65 mmHg. WBC 14.5 ± 11.9 K/ml . Hb 12.5± 3.1 mg/dl. BUN 32.2± 33 mg/dl. SC 2.2± 3.3 mg/dl. HbA1C 13.8 ± 6.4 g%. Cholesterol 173.7 ± 61.6 mg/dl. HDL-cholesterol 39.06 ± 28.0 mg/dl. LDL-cholesterol 115.0 ± 55 mg/dl. trigliserida 138.8 ± 71.5 mg/dl, Fasting BS 196.6 ± 94 mg/dl, after meal BS 243.2 ± 110 mg/dl. We found 36 patient UTI (36%) with upper UTI 9 (25%). Lower UTI 27 (75%). Asymptomatic bacteriuria 25 (69.4%). Symptomatic bacteriuria 11 (30.6%). About 2.8% of recurrent UTI. Prevalence of UTI in patients less than 50 yo. were more than patient above 50 yo. UTI in women were higher than men. We found E. coli 30.5%, S. epidermidis 27.7% S. aureus 11.1%, E. zakazakii, and S. marcescens, C. albican respectly 5.5%, S. coagulase, S. liquyacians, E. cloaceae, E. hapniae, C. violaleum respectly 2.7%. as cause UTI this study. We found Sensitivity test with antibiotic, imipenem 23%, amoxicillin-clavulamic acid 20%, ceftazidin 19%, gentamisin 19%, cefoxitin 17%, piperacillin/ tazobactam 14%, sulphamethoxazol, ofloxasin, ceftriaxon 13% respectly, cefuroxime 12%, cifroploxasin 11%, ampicilin, linezolide 6% respectly. vancomisin 4%, cephazolin, cefoperazone-sulbactam 3% respectedly. meticilin, cefoperazone, erithromisin, amoxillin, oxacilin respectly 1%. We found E. coli 100% sensitive with imepenem, amoxicillin-clavulamic acid, piperasillin-tazobactam. 90.9% Sensitivity for ceftazidin, gentamycin. From six independen variabel (dyslipidemia, BMI catagori, hipertension, sex, age, blood sugar controled, stone in urinary tract, chronic renal disease, lung TB, pneumonia, cancer, user of chateterization) only BMI significant correlation (X2 = 13.8, p= 0.03 OR= 2.14) with prevalence UTI in patient DM.
Keywords: urogenital tract infection, diabetes mellitus, cultur & sensitivity test